KEMASAN PAKET WISATA JATILUWIH SIGHTSEEING AND ADVENTURE - Sri Lestari, Renita; Oka Karini, Ni Made; Sasrawan Mananda, I GPB. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 2 No 2 (2014): Jurnal IPTA (December 2014)DO - 10.24843/IPTA.2014.v02.i02.p01)
This study discusses and examines potential identification and package tour in Tabanan regency. Qualitative approaches were applied in this research. The data were collected by using observation techniques, in-depths interviews, and documentation technique. Informant and key informant techniques were used to determine the informantion. This study used descriptive qualitative data analysis techniques with three steps which are data reduction, data display and conclusion drawing. In this study, showed potential identifications taken place in Alas Kedaton, Jatiluwih, Batukaru Temple, Subak Museum, and Tengkudak Village. The packaging of this package tour with itinerary such as visit the Subak Museum, Tengkudak village adventure, visit Jatiluwih, sightseeing in Batukaru temple, sightseeing in Alas Kedaton and shopping in Krisna oleh-oleh. This package tour was presented in tabulated style, Graphic style as well as the calculation of travel costs.
Keywords: The Packaging, Package Tour, Tourist Potential